A Study to Assess the Effectiveness of Information Booklet on Selected Behavioral Problems among School Going Children in Terms of Knowledge of Selected Schools of Primary Schools Teachers of Pune City - Rutuja Bhagwan Vairat1 , Nilima Suryakant Shinde1 , Amol Sanjay Gaikwad1 , Vishal Rajendra Chabukswa (Indian Journal of Forensic Medicine & Toxicology, 2020)
Behavioural problems are refers to as the abnormal behaviour or abnormality of emotions, behaviour orrelationship. The problems may be sever or mild. But the behavioural problems are sufficiently sever &persistent to handicap the child in his social or personal functioning & to cause distress to the child.The present study assessed the effectiveness of Information Booklet on selected Behavioural problemsamong school going children in terms of knowledge of selected schools of primary schools teachers.Majority of subjects were (20%) were in age group of 25-30 years and 13.3% samples are from age groupof 36-40 years. 33.33% sample’s educational qualification was post graduate, 20.06% sample’s educationalqualification was graduate and 13.33% sample’s educational qualification were higher secondary. 66.6%sample’s work experience was above 12 years, 6.66% sample’s work experience was 7-12 years, 16.60%sample’s work experience was 4-6 years, and only 10% sample’s work experience was 0-3 years. On the basisof gender, 96.66% of samples were females and 3.34% were male. T-test was used to assess the effectivenessof informational booklet regarding behaviour problems and p-value was found to be less than ? (p= .031).